Archaic Deixis Expressions in Wuthering Heights and Their Equivalence in Modern English - Valentina, Febrila Kristi; Sunarto, E. Sunarto (CV. Tripe Konsultan, 2025)
This study examined archaic pronouns in the selected passages of Wuthering Heights, with a specific focus on the pronouns 'ye,' 'thy,' 'thee,' and 'thou.' The objective is to explore the different types of archaic pronouns used by characters and what their equivalents are in modern English. Through a qualitative analysis, the research explores how they functioned in Early Modern English reflected in the novel and how they correspond to pronouns in modern English. The findings reveal that 'ye' occurs 13 times, 'thy' 6 times, 'thee' 5 times, and 'thou' 4 times. In terms of modern equivalents, 'ye' corresponds to 'you' (plural), 'thy' to 'your' (possessive), 'thee' is replaced by 'you' (object), and 'thou' corresponds to 'you' (subject, informal). The study concludes that the shift from these archaic pronouns to the standardization of contemporary 'you' and 'your' reflects both grammatical simplification and social changes, signifying the loss of distinctions between singular and plural forms, as well as formal and informal addresses in English. The results highlight the evolution of English towards a more uniform structure, driven by cultural and linguistic developments.